Design and manufacturing of the tilt-rotor bicopter VTOL UAV using 3D printing - Yi, Wan (2018)
Amongst the two main types of fixed-wing vertical-takeoff-and-landing (FW-VTOL) unmanned aerial vehicles (UAVs) namely, hybrid FW multi-copter UAVs and tilt rotor FW-VTOL UAVs, the latter is usually preferred due to its efficient propulsion system that is utilized for all flight phases. Howbeit, in the currently available tilt-rotor FW-VTOL UAVs, one or more rotors are turned off during the FW mode, which eventually acts as a dead weight for the UAV. Therefore, in this project, we design a tilt-rotor FW-VTOL UAV which encompasses a dual-rotor configuration. A detailed design is carried out from sizing, configuration, aerodynamics, propulsion, dynamics, structures to electronics. Multiple prototypes are constructed and additive manufacturing (AM) is used as the primary manufacturing method. The high strength and rapid prototyping features of AM are utilized in our design to achieve adequate structural strength without inducing weight penalties. What is more, flight tests are conducted to verify the design feasibility. The results exhibit that the tilt-rotor dual rotor configuration is a successful solution to FW-VTOL UAVs. The results also prove that AM is a promising manufacturing method for complex FW-VTOL UAVs, wherein its on-demand printing ability significantly lowers the overall development cost.